Study of the polyphenolic compounds accumulation in Thymus serpyllum L. herb during the flowering period - Mazulin, O. V.; Fukleva, L. A.; Mazulin, G. V.; Мазулін, Олександр Владиленович; Фуклева, Лариса Анатоліївна; Мазулін, Георгій Владиленович (My University, 2023)
The Thymus serpyllum L. is a widespread in the steppe bioсenosеs of southern and eastern Ukraine. It is well cultivated in specialized farms. A promising direction of modern phytochemical research of wild and cultivated Thymus L. species is the determination of the accumulation of biologically active polyphenolic compounds that exhibit pronounced biological activity. The purpose of the work is to determine the accumulation of polyphenolic compounds in Thymus serpyllum L. herb at the flowering using TLC and HPLC methods. The Thymus serpyllum L. herb was harvested in steppe biocenoses of southern and eastern Ukraine at the flowering, during the period of biologically active polyphenolic compounds maximum accumulation. For experimental studies, alcohol extracts from Thymus serpyllum L. herb (1:100) were used. The substances component composition was studied by TLC method Biostep CD 60 densitometer (Germany) and HPLC Agilent 1260 Infinity HPLC System Open LABCDS Software (Japan). TLC and HPLC methods revealed up to 25 polyphenolic compounds. Experimentally were determined 13 flavonoids and 12 hydroxycinnamic acids. All these biologically active compounds are well known in modern phytotherapy for their pronounced antimicrobial, anti-inflammatory and antioxidant activity. During the flowering period up to 25 polyphenolic compounds were identified and quantified in the ethanolic extract (1:100) obtained from Thymus serpyllum L. herbal raw material. Of these, 13 compounds were attributed to flavonoids with a defined total content (0.3 mg/100 mg) and 12 to hydroxycinnamic acids (0.9 mg/100 mg). The highest accumulation of hydroxycinnamic acids in the Thymus serpyllum L. herbal raw material were characterized by rosmarinic acid (12.77 + 1.19%), chlorogenic acid (8.55 + 0.79%) and p-coumaric acid (7.41 + 0.69%). Of flavonoids, the highest content were established for rutin (8.45 + 0.79%), luteolin (3.87 + 0.37%), luteolin-7-O-β-D-glucopyranoside (3.86 ± 0.33%), apigenin-7,4’-diglucoside (3.86 ± 0.32%), quercetin (3.85 ± 0.34%) and apigenin (3.81 ± 0.36%). The results obtained by TLC and HPLC methods indicate the perspective of polyphenolic compounds research for the purpose of determining the biological activity of extracts and carrying out the standardization of Thymus serpyllum L. herb. The study of the polyphenolic compounds accumulation in the Thymus serpyllum L. plant raw materials is important for this standardization and obtaining effective phytopreparations. Чебрець повзучий (Thymus serpyllum L.) є розповсюдженим дикорослим видом у степових біоценозах півдня та сходу України. Успішно культивується у спеціалізованих господарствах. Перспективним напрямом сучасних фітохімічних досліджень дикорослих та культивованих видів роду Thymus L. є визначення накопичення біологічно активних поліфенольних сполук, які виявляють виражену біологічну активність. Мета роботи – методами ТШХ та ВЕРХ визначити накопичення поліфенольних сполук у траві чебрецю повзучого під час цвітіння. Траву чебрецю повзучого заготовляли у степових біоценозах півдня та сходу України в кінці цвітіння під час максимального накопичення біологічно активних речовин. Для визначення присутності поліфенольних сполук та їх кількісного вмісту використовували спиртові витяги з трави виду (1:100). Компонентний склад досліджували методом ТШХ на денситометрі Biostep CD 60 (Німеччина) та ВЕРХ на хроматографі Agilent 1260 Infinity HPLC System Open LABCDS Software (Японія). Методом ТШХ та ВЕРХ було ідентифіковано до 25 речовин поліфенольної природи. Встановлено кількісний вміст 13 флавоноїдів та 12 гідроксикоричних кислот, для яких за фітотерапевтичного призначення притаманна виражена протизапальна, антимікробна та антиоксидантна активність. Під час цвітіння в етанольному екстракті (1:100), одержаному з трави Thymus serpyllum L., було ідентифіковано та визначено кількісний вміст до 25 сполук поліфенольної природи. Із них було 13 віднесено до флавоноїдів із визначеним загальним вмістом (0,5 мг/100 мг) та 12 – до гідроксикоричних кислот (1,5 мг/100 мг). Найбільше накопичення з гідроксикоричних кислот у траві досліджуваного виду було притаманне для розмаринової кислоти (12,77 ± 1,19%), хлорогенової (8,55 ± 0,79%) та п-кумарової (7,41 ± 0,69%). Із флавоноїдів найбільший вміст встановлено для рутину (8,45 ± 0,79%), лютеолину (3,87 ± 0,37%), лютеолин-7-О-β-D-глюкопиранозиду (3,86 ± 0,33%), апігенін-7,4’-диглюкозиду (3,86 ± 0,32%), кверцетину (3,85 ± 0,34%) та апігеніну (3,81 ± 0,36%). Результати, одержані методами ТШХ та ВЕРХ, свідчать про перспективність дослідження біологічної активності екстрактів та проведення стандартизації трави Thymus serpyllum L. за накопиченням поліфенольних сполук. Дослідження накопичення поліфенольних сполук у траві видів роду Thymus L. має важливе значення для заготівлі рослинної сировини та одержання фітопрепаратів на її основі.
Вивчення накопичення поліфенольних сполук у траві чебрецю повзучого (Thymus serpyllum L.) під час цвітіння
Keywords: Thymus serpyllum L.; herb; polyphenolic compounds; accumulation; TLC and HPLC methods; flowering period; чебрець повзучий; трава; поліфенольні сполуки; накопичення; методи ТШХ та ВЕРХ; час цвітіння